Renewable Energy Powered Membrane Technology: Electrical Energy Storage Options for a Photovoltaic-Powered Brackish Water Desalination System - Sheying Li; Ana P. S. G. de Carvalho; Andrea I. Schäfer; Bryce S. Richards (Applied Sciences, 2021)
The potential for lithium-ion (Li-ion) batteries and supercapacitors (SCs) to overcome long-term (one day) and short-term (a few minutes) solar irradiance fluctuations with high-temporal-resolution (one s) on a photovoltaic-powered reverse osmosis membrane (PV-membrane) system was investigated. Experiments were conducted using synthetic brackish water (5-g/L sodium chloride) with varied battery capacities (100, 70, 50, 40, 30 and 20 Ah) to evaluate the effect of decreasing the energy storage capacities. A comparison was made between SCs and batteries to determine system performance on a “partly cloudyday”. With fully charged batteries, clean drinking water was produced at an average specific energy consumption (SEC) of 4 kWh/m3. The daily water production improved from 663 L to 767 L (16% increase) and average electrical conductivity decreased from 310 µS/cm to 274 μS/cm (12% improvement), compared to the battery-less system. Enhanced water production occurred when the initial battery capacity was >50 Ah. On a “sunny” and “very cloudy” day with fully charged batteries, water production increased by 15% and 80%, while water quality improved by 18% and 21%, respectively. The SCs enabled a 9% increase in water production and 13% improvement in the average SEC on the “partly cloudy day” when compared to the reference system performance (without SCs).